Refractory material, preparation method and application thereof, refractory brick and glass melting furnace
By using refractory materials prepared with specific ratios of fused zirconium mullite, alumina powder and zirconia powder, forming a frame structure and filling the glass phase, the lack of performance of traditional refractory materials in high temperature and chemical erosion environments is solved, and efficient thermal shock and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510020607.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Traditional refractory materials have problems such as high foaming rate, poor corrosion resistance and insufficient thermal shock resistance in high temperature and chemical erosion environments, which affect the normal operation of glass melting kilns and the quality of glass products.
A specific ratio of fused zirconium mullite, alumina powder and zirconium oxide powder are used as preparation materials. A frame structure mainly consisting of mullite crystal phase is formed by sintering treatment, and the glass phase is filled with low melting point components to reduce porosity and improve thermal vibration resistance and corrosion resistance.
Refractory materials with low foaming rate and good corrosion resistance are achieved, the materials' thermal shock resistance and glass liquid corrosion resistance are improved, and the normal operation of the glass melting kiln and the quality of glass products are ensured.
Smart Images

Figure CN119822822A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of refractory materials, and in particular to a refractory material and a preparation method and application thereof, refractory bricks and a glass melting furnace. Background Art
[0002] The photovoltaic glass industry is currently in a stage of rapid development, and the future development trend is very optimistic. To produce high-quality photovoltaic glass, not only mature process conditions are required, but also the corresponding production equipment has an important impact on the quality of the glass. For example, the glass melting furnace; its main function is to heat the glass raw materials (such as quartz sand, soda ash, limestone, etc.) to high temperature, melt them and mix them evenly to form glass liquid that meets the quality requirements.
[0003] Lip bricks are located at the interface between glass liquid and furnace gas in the glass melting furnace, that is, the "lip" of the glass melting furnace. This position is the edge of the channel where the glass liquid enters and exits the melting furnace. The shape of the lip brick is generally long and strip-shaped, with one side in contact with the glass liquid and the other side exposed to the furnace gas; the main function of the lip brick is to control the flow of glass liquid and guide the glass liquid in and out of the melting furnace. Lip bricks are generally made of refractory materials; at the same time, because the lip bricks are in a high temperature and chemically corrosive environment, they need to have good corrosion resistance and thermal shock resistance to prevent erosion by chemical components in the glass liquid and furnace gas, thereby ensuring the normal operation of the glass melting furnace and the quality of glass products. In addition, the foaming rate of the lip brick is also a key factor affecting the quality of glass.
[0004] Therefore, traditional technology needs to be improved. Summary of the invention
[0005] Based on this, it is necessary to provide a refractory material with low foaming rate, good corrosion resistance and good thermal shock resistance, as well as its preparation method, application, refractory bricks and glass melting furnace.
[0006] In a first aspect, the present application provides a refractory material, wherein the raw materials for preparing the refractory material include the following components by mass: 55 to 80 parts of fused zirconium mullite, 10 to 15 parts of zirconium oxide powder, and 10 to 30 parts of aluminum oxide powder.
[0007] The above-mentioned refractory material is prepared by using raw materials containing fused zirconium mullite, alumina powder and zirconium oxide powder in a specific ratio; wherein, fused zirconium mullite has good thermal vibration resistance and low porosity, which provides a basis for the low porosity and thermal vibration resistance of the refractory material; on this basis, the fused zirconium mullite alumina powder and zirconium oxide powder are synergistically mixed in the above-mentioned specific ratio, and after sintering, a crystal phase structure dominated by mullite crystal phase can be formed, and the crystal phase structure also includes zircon phase and corundum eutectoid and baddeleyite crystal, and these crystal phase structures are intertwined to form a frame structure, which is beneficial to improve the strength and thermal vibration resistance of the refractory material. Moreover, some low-melting-point components in the fused zirconium mullite can exist in the molten glass phase during the sintering process and fill in the lattices of each crystal phase, so that the product has a compact structure, which is beneficial to reduce the porosity and improve its resistance to glass liquid erosion. In this way, a refractory material with a low foaming rate, good erosion resistance and good thermal shock resistance is provided.
[0008] In some embodiments, the refractory material contains a crystalline phase including a mullite phase, a corundum phase, a baddeleyite phase, and a zircon phase.
[0009] In some embodiments, in the refractory material, the crystalline phase includes, by mass content, 45% to 50% of a mullite phase, 17% to 20% of a corundum phase, 20% to 23% of a baddeleyite phase, and 10% to 13% of a zircon phase.
[0010] In some embodiments, the refractory material satisfies at least one of the following conditions:
[0011] (1) The porosity of the fused zirconium mullite is 16% to 17.5%;
[0012] (2) The components in the fused zirconium mullite meet the following conditions: the mass fraction of ZrO2 is greater than 32.5%, the mass fraction of Al2O3 is greater than 42%, the mass fraction of SiO2 is ≤18%, the mass fraction of TiO2 is ≤0.2%, the mass fraction of Fe2O3 is ≤0.2%, the total mass fraction of Na2O and K2O is ≤0.35%, and the total mass fraction of CaO and MgO is ≤0.35%;
[0013] (3) The components in the alumina powder meet the following conditions: the mass fraction of Al2O3>98.5%, the mass fraction of SiO2<0.3%, the mass fraction of Fe2O3≤0.1%, and the total mass fraction of Na2O and K2O≤0.35%; the ignition loss of the alumina powder is less than 0.5%;
[0014] (4) The components in the zirconium oxide powder meet the following conditions: the mass fraction of ZrO2 is greater than 65.5%, the mass fraction of SiO2 is less than 34%, the mass fraction of Fe2O3 is less than or equal to 0.2%, and the mass fraction of TiO2 is less than or equal to 0.35%.
[0015] In some embodiments, the refractory material satisfies at least one of the following conditions:
[0016] (1) The fused zirconium mullite includes fused zirconium mullite coarse material with a particle size greater than 3 mm and less than or equal to 5 mm, fused zirconium mullite medium material with a particle size greater than 1.5 mm and less than or equal to 3 mm, fused zirconium mullite fine material with a particle size greater than 0.5 mm and less than or equal to 1.5 mm, fused zirconium mullite ultrafine material with a particle size greater than 0.1 mm and less than or equal to 0.5 mm, and fused zirconium mullite powder with a D50 of 10 μm to 20 μm;
[0017] (2) The D50 of the zirconium oxide powder is 5 μm to 15 μm;
[0018] (3) The alumina powder includes alumina powder A with a D50 of 1.5 μm to 2.5 μm and alumina powder B with a D50 of 3 μm to 6 μm.
[0019] In some embodiments, the following raw materials are included by weight:
[0020] 10 to 35 parts of the fused zirconium mullite coarse material,
[0021] 5 to 25 parts of the fused zirconium mullite medium material,
[0022] 3 to 15 parts of the fused zirconium mullite fine material,
[0023] 15 to 25 parts of the fused zirconium mullite ultrafine material,
[0024] 5 to 10 parts of the fused zirconium mullite powder,
[0025] 8 to 20 parts of the aluminum oxide powder A,
[0026] 2 to 10 parts of the aluminum oxide powder B, and
[0027] The zirconium oxide powder is 10 to 15 parts.
[0028] In some embodiments, the alumina powder A is composed of 40% to 60% alumina powder A1 and 40% to 60% alumina powder A2 in terms of mass percentage; the D50 of the alumina powder A1 is 2 μm ± 0.1 μm; and the D50 of the alumina powder A2 is 2.3 μm ± 0.1 μm.
[0029] In some embodiments, the refractory material satisfies at least one of the following conditions:
[0030] (1) The raw materials for preparation further include 0.2 to 0.4 parts of a dispersion enhancer;
[0031] (2) The preparation raw materials also include 5 to 7 parts of water.
[0032] In some embodiments, the dispersion enhancer is an inorganic clay; the inorganic clay satisfies at least one of the following conditions:
[0033] (1) The components in the inorganic clay meet the following conditions: the mass fraction of Al2O3 is less than 15%, the mass fraction of SiO2 is greater than 50%, the mass fraction of CaO is ≤5%, and the mass fraction of MgO is ≤25%;
[0034] (2) The D50 of the inorganic clay is 3 μm to 15 μm;
[0035] (3) The inorganic clay includes at least one of attapulgite and kaolin.
[0036] In a second aspect of the present application, a method for preparing the above-mentioned refractory material is provided, comprising the following steps:
[0037] The raw materials are mixed and then cast to obtain a blank;
[0038] The blank is calcined to obtain the refractory material.
[0039] In some embodiments, the preparation method satisfies at least one of the following conditions:
[0040] (1) The casting molding adopts vacuum casting molding; the vacuum degree of vacuum casting molding is -0.08MPa~-0.1MPa; the molding pressure is: 0.2MPa~0.4MPa;
[0041] (2) Before calcining the blank, the method further comprises drying the blank;
[0042] The drying step comprises: firstly air-drying the blank for 120 hours to 240 hours, and then drying at 40° C. to 80° C. for 48 hours to 96 hours;
[0043] (3) The calcination temperature is 1300°C to 1500°C; the calcination time is 8h to 15h.
[0044] In a third aspect, the present application provides a use of the above-mentioned refractory material in the preparation of refractory products.
[0045] In a fourth aspect of the present application, a refractory brick is provided, comprising the refractory material described in the first aspect of the present application.
[0046] In a fifth aspect of the present application, a glass melting furnace is provided, comprising the refractory bricks described in the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are merely embodiments of the present application, and ordinary technicians in this field can obtain other drawings based on the disclosed drawings without paying any creative work.
[0048] Figure 1 This is a surface picture of the refractory brick prepared in Example 3 after the foaming test.
[0049] Figure 2 This is a surface picture of the refractory brick prepared in Comparative Example 1 after the foaming experiment.
[0050] Figure 3 This is a graph showing the glass erosion resistance of the refractory bricks prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0051] In order to facilitate the understanding of the present invention, the present invention is described more comprehensively below. And preferred embodiments of the present invention are given. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. It should be understood that the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0053] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0054] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0055] In one embodiment of the present application, a refractory material is provided, wherein the raw materials for preparing the refractory material include the following components by mass: 55 to 80 parts of fused zirconium mullite, 10 to 15 parts of zirconium oxide powder, and 10 to 30 parts of aluminum oxide powder.
[0056] The above-mentioned refractory material contains a specific ratio of fused zirconium mullite, alumina powder and zirconium oxide powder; among them, the fused zirconium mullite has good thermal vibration resistance and low porosity, and the low porosity and thermal vibration resistance of the refractory material provide the basis; and some low-melting-point components in the fused zirconium mullite can exist in the molten glass phase. After sintering, the fused zirconium mullite, alumina powder and zirconium oxide powder in the above-mentioned specific ratio can form a crystal phase structure dominated by mullite crystal phase, followed by the eutectic of zircon phase and corundum and baddeleyite crystals, which are intertwined to form a framework structure, thereby improving the strength and thermal vibration resistance of the refractory material. Furthermore, the low-melting-point substance in the fused zirconium mullite is filled between the lattices of each crystal phase in the form of a glass phase, so that the product has a compact structure, low porosity and resistance to glass liquid erosion.
[0057] In some embodiments, the refractory material contains crystalline phases including a mullite phase, a corundum phase, a baddeleyite phase, and a zircon phase.
[0058] In some embodiments, in the refractory material, the crystalline phase includes, by mass content, 45% to 50% of a mullite phase, 17% to 20% of a corundum phase, 20% to 23% of a baddeleyite phase, and 10% to 13% of a zircon phase.
[0059] In some embodiments, the thermal shock resistance of fused zirconium mullite with a thickness of 65 mm, a length of 230 mm, and a width of 114 mm at 1100° C. is 30 to 50 times.
[0060] In some embodiments, the porosity of the fused zirconium mullite is 16% to 17.5%.
[0061] In some embodiments, the components in the fused zirconium mullite satisfy the following conditions: the mass fraction of ZrO2 is greater than 32.5%, the mass fraction of Al2O3 is greater than 42%, the mass fraction of SiO2 is ≤18%, the mass fraction of TiO2 is ≤0.2%, the mass fraction of Fe2O3 is ≤0.2%, the total mass fraction of Na2O and K2O is ≤0.35%, and the total mass fraction of CaO and MgO is ≤0.35%. Further, in the fused zirconium mullite, the mass fraction of ZrO2 is greater than 32.5% and less than 40%, the mass fraction of Al2O3 is greater than 42% and less than 50%, the mass fraction of SiO2 is greater than 15% and less than or equal to 18%, the mass fraction of TiO2 is greater than or equal to 0.1% and less than or equal to 0.2%, the mass fraction of Fe2O3 is less than 0.2%, the total mass fraction of Na2O and K2O is greater than or equal to 0.1% and less than 0.35%, and the total mass fraction of CaO and MgO is greater than or equal to 0.1% and less than 0.35%.
[0062] In some embodiments, the components in the alumina powder meet the following conditions: the mass fraction of Al2O3>98.5%, the mass fraction of SiO2<0.3%, the mass fraction of Fe2O3≤0.1%, and the total mass fraction of Na2O and K2O≤0.35%. Further, in the alumina powder, the mass fraction of Al2O3 is greater than 98.5% and less than 99.5%, the mass fraction of SiO2 is greater than 0.05% and less than 0.3%, the mass fraction of Fe2O3 is greater than 0.02% and less than 0.1%, and the total mass fraction of Na2O and K2O is greater than 0.12% and less than 0.35%.
[0063] In some embodiments, the ignition loss of the aluminum oxide powder is less than 0.5%. Preferably, the ignition loss of the aluminum oxide powder is 0.05% to 0.1%.
[0064] In some embodiments, the components in the zirconium oxide powder meet the following conditions: the mass fraction of ZrO2>65.5%, the mass fraction of SiO2<34%, the mass fraction of Fe2O3≤0.2%, and the mass fraction of TiO2≤0.35%. Preferably, in the zirconium oxide powder, the mass fraction of ZrO2 is greater than 90% and less than 99.9%, the mass fraction of SiO2 is and less than 0.5%, the mass fraction of Fe2O3 is greater than 0.01% and less than 0.1%, and the mass fraction of TiO2 is greater than 0.1% and less than 0.35%.
[0065] In some embodiments, the fused zirconium mullite includes fused zirconium mullite coarse material with a particle size greater than 3 mm and less than or equal to 5 mm, fused zirconium mullite medium material with a particle size greater than 1.5 mm and less than or equal to 3 mm, fused zirconium mullite fine material with a particle size greater than 0.5 mm and less than or equal to 1.5 mm, fused zirconium mullite ultrafine material with a particle size greater than 0.1 mm and less than or equal to 0.5 mm, and fused zirconium mullite micropowder with a D50 of 10 μm to 20 μm. The fused zirconium mullite is added in different particle sizes, and the finer powder can fill the voids, making the refractory material more dense and reducing the porosity of the refractory material; it can also further inhibit the shrinkage of the refractory material.
[0066] D50 in this application refers to the median particle size.
[0067] In some embodiments, the components of the fused zirconium mullite coarse material, the fused zirconium mullite medium material, the fused zirconium mullite fine material, the fused zirconium mullite ultrafine material and the fused zirconium mullite micropowder may be the same or different, but all must meet the above-mentioned component conditions of the fused zirconium mullite.
[0068] In some embodiments, the D50 of the zirconium oxide powder is 5 μm to 15 μm.
[0069] In some embodiments, the aluminum oxide powder includes aluminum oxide powder A having a D50 of 1.5 μm to 2.5 μm and aluminum oxide powder B having a D50 of 3 μm to 6 μm.
[0070] In some embodiments, the following raw material components are included by weight:
[0071] 10~35 parts of fused zirconium mullite coarse material,
[0072] 5~25 parts of fused zirconium mullite medium material,
[0073] 3 to 15 parts of fused zirconium mullite fine material,
[0074] 15~25 parts of fused zirconium mullite ultrafine material,
[0075] 5~10 parts of fused zirconium mullite powder,
[0076] Alumina powder A 8~20 parts,
[0077] Alumina powder B 2~10 parts,
[0078] 10 to 15 parts of zirconium oxide powder, and
[0079] 5 to 7 parts water.
[0080] As an example, the mass fraction of the fused zirconium mullite coarse material can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or 35 parts. Further, the mass fraction of the fused zirconium mullite coarse material can be a range value consisting of any two of the above point values as end values. Preferably, the mass fraction of the fused zirconium mullite coarse material is 20 parts to 30 parts. More preferably, the mass fraction of the fused zirconium mullite coarse material is 25 parts to 30 parts.
[0081] As an example, the mass fraction of the fused zirconium mullite medium material can be 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, or 25 parts. Further, the mass fraction of the fused zirconium mullite medium material can be a range value consisting of any two of the above point values as end values. Preferably, the mass fraction of the fused zirconium mullite medium material is 8 parts to 17 parts. More preferably, the mass fraction of the fused zirconium mullite coarse material is 10 parts to 17 parts.
[0082] As an example, the mass fraction of the fused zirconium mullite fine material can be 3 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 12 parts, 14 parts or 15 parts. Further, the mass fraction of the fused zirconium mullite fine material can be a range value consisting of any two of the above point values as end values. Preferably, the mass fraction of the fused zirconium mullite fine material is 4 parts to 6 parts.
[0083] As an example, the mass fraction of the fused zirconium mullite ultrafine material can be 15 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts or 25 parts. Further, the mass fraction of the fused zirconium mullite ultrafine material can be a range value consisting of any two of the above point values as end values. Preferably, the mass fraction of the fused zirconium mullite ultrafine material is 19 parts to 21 parts.
[0084] As an example, the mass fraction of the fused zirconium mullite powder can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. Further, the mass fraction of the fused zirconium mullite powder can be a range value consisting of any two of the above point values as end values. Preferably, the mass fraction of the fused zirconium mullite powder can be 5 parts to 7 parts.
[0085] As an example, the mass fraction of aluminum oxide powder A can be 8, 10, 11, 12, 14, 15, 16, 18, 19 or 20. Further, the mass fraction of aluminum oxide powder A can be a range value consisting of any two of the above point values as end values.
[0086] In some embodiments, the alumina powder A is composed of 40% to 60% of alumina powder A1 and 40% to 60% of alumina powder A2; wherein the D50 of the alumina powder A1 is 2±0.1 μm; and the D50 of the alumina powder A2 is 2.3±0.1 μm. The components of the alumina powder A are further controlled to be added in different median particle sizes, which is beneficial to the structure and sintering of the product.
[0087] In some embodiments, the refractory material comprises 5 to 10 parts of alumina powder A1 and 5 to 10 parts of alumina powder A2 by weight.
[0088] As an example, the mass fraction of aluminum oxide powder B can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. Further, the mass fraction of aluminum oxide powder B can be a range value consisting of any two of the above point values as end values. Preferably, the mass fraction of aluminum oxide powder B can be 3 parts to 5 parts.
[0089] It can be understood that the chemical compositions of the aluminum oxide powder A1, aluminum oxide powder A2 and aluminum oxide powder B can be the same or different, but they all need to meet the above conditions.
[0090] As an example, the mass fraction of zirconium oxide powder can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts. Further, the mass fraction of zirconium oxide powder can be a range value consisting of any two of the above point values as end values. Preferably, the mass fraction of zirconium oxide powder can be 12 parts to 14 parts.
[0091] In some embodiments, the raw materials for preparing the refractory material further include 0.2 to 0.4 parts of a dispersion enhancer.
[0092] In some embodiments, the dispersion enhancer is inorganic clay. Using inorganic clay as a dispersion enhancer can make the mud material have better dispersibility and suspension, prevent particle sedimentation and do not affect fluidity.
[0093] In some embodiments, the components in the inorganic clay meet the following conditions: the mass fraction of Al2O3 is less than 15%, the mass fraction of SiO2 is greater than 50%, the mass fraction of CaO is ≤5%, and the mass fraction of MgO is ≤25%.
[0094] In some embodiments, inorganic clays include, but are not limited to, attapulgite.
[0095] In some embodiments, the D50 of the inorganic clay is 3 μm to 15 μm. Preferably, the D50 of the inorganic clay is 5 μm to 12 μm. More preferably, the D50 of the inorganic clay is 8 μm to 11 μm.
[0096] In some embodiments, the raw materials for preparing the refractory material further include 5 to 7 parts of water. Adding water is beneficial to molding.
[0097] In some embodiments, the raw materials for preparing the refractory material include, by weight:
[0098] 20~35 parts of fused zirconium mullite coarse material,
[0099] 8~17 parts of fused zirconium mullite medium material,
[0100] 4~6 parts of fused zirconium mullite fine material,
[0101] 19~21 parts of fused zirconium mullite ultrafine material,
[0102] 5~7 parts of fused zirconium mullite powder,
[0103] Alumina powder A1 5~10 parts,
[0104] Alumina powder A2 5~10 parts,
[0105] Alumina powder B 3~5 parts,
[0106] Zirconium ball powder 12~14 parts,
[0107] 0.2 to 0.4 parts of attapulgite, and
[0108] 5 to 7 parts water.
[0109] In some embodiments, the raw materials for preparing the refractory material include, by weight:
[0110] 25~35 parts of fused zirconium mullite coarse material
[0111] 10~17 parts of fused zirconium mullite medium material
[0112] 4~6 parts of fused zirconium mullite fine material,
[0113] 19~21 parts of fused zirconium mullite ultrafine material,
[0114] 5~7 parts of fused zirconium mullite powder,
[0115] Alumina powder A1 5~10 parts,
[0116] Alumina powder A2 5~10 parts,
[0117] Alumina powder B 3~5 parts,
[0118] Zirconia powder 12~14 parts,
[0119] 0.2 to 0.4 parts of attapulgite, and
[0120] 5.5 to 6.5 parts water.
[0121] In another embodiment of the present application, a method for preparing a refractory material is provided, comprising the following steps S10 to S30.
[0122] S10, mixing the raw material components.
[0123] In some embodiments, the step of mixing the raw material components comprises:
[0124] First, the fused zirconium mullite, alumina powder and zirconium oxide powder are mixed for 3 minutes to 5 minutes; then water is added and wet mixed for 4 minutes to 7 minutes to obtain mud.
[0125] S20, after the mixing is completed, casting is performed to obtain a blank.
[0126] In some embodiments, the casting is performed by vacuum casting. Vacuum casting can improve the density and mechanical strength of the refractory material, reduce defects such as pores and inclusions, and further improve the corrosion resistance of the refractory material. In addition, the size and shape of the refractory material can be precisely controlled to improve the accuracy and consistency of the product.
[0127] In some embodiments, when vacuum casting is used, the vacuum degree is -0.08MPa~-0.1MPa.
[0128] In some embodiments, when vacuum casting is used, the molding pressure is 0.2MPa~0.4MPa.
[0129] S30, calcining the blank to obtain a refractory material.
[0130] In some embodiments, the calcination temperature is 1300°C to 1500°C. As an example, the calcination temperature may be 1300°C, 1320°C, 1350°C, 1360°C, 1380°C, 1400°C, 1420°C, 1450°C, 1480°C or 1500°C. Further, the calcination temperature may be a range value consisting of any two of the above point values as end values. Preferably, the calcination temperature is 1380°C to 1420°C.
[0131] In some embodiments, the calcination time is 8 hours to 15 hours. As an example, the calcination time can be 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours. Further, the calcination time can be a range value consisting of any two of the above point values as end values. Preferably, the calcination time can be 9 hours to 11 hours.
[0132] In some embodiments, before calcining the ingot, the process further includes drying the ingot.
[0133] In some embodiments, the step of drying the blank comprises:
[0134] First, air dry the blanks for 120h~240h, and then dry them at 40℃~80℃ for 48h~96h.
[0135] In another embodiment of the present application, there is provided a use of the above refractory material in preparing refractory products. The refractory products include but are not limited to refractory bricks.
[0136] The application scenarios of refractory bricks include but are not limited to glass melting furnaces. For example, they can be used as lip bricks in glass melting furnaces.
[0137] In yet another embodiment of the present application, a refractory brick is provided. The lip brick comprises the above-mentioned refractory material.
[0138] In yet another embodiment of the present application, a glass melting furnace is provided. The glass melting furnace includes the above-mentioned lip brick.
[0139] In order to make the purpose, technical solutions and advantages of the present invention more concise and clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present invention, which can be used to describe the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0140] In order to better illustrate the present invention, the present invention is further described below in conjunction with the embodiments. The following are specific embodiments.
[0141] The raw materials used in the examples and comparative examples are as follows:
[0142] The fused zirconium mullite includes the following components: the mass fraction of ZrO2 is 35-38%, the mass fraction of Al2O3 is 43-47%, the mass fraction of SiO2 is 16-18%, the mass fraction of TiO2 is 0.1-0.2%, the mass fraction of Fe2O3 is 0-0.2%, the total mass fraction of Na2O and K2O is 0.1-0.3%, and the total mass fraction of CaO and MgO is 0.1-0.3%. The product was purchased from Henan Changcheng Special High-tech Materials Co., Ltd.
[0143] The fused zirconium mullite of the above components is crushed by a crusher and then sieved by a screen to obtain the following fused zirconium mullite with different particle sizes:
[0144] Fused zirconium mullite coarse material: greater than 3mm and less than or equal to 5mm;
[0145] Fused zirconium mullite medium material: greater than 1.5mm and less than or equal to 3mm;
[0146] Fused zirconium mullite fine material: greater than 0.5mm and less than or equal to 1.5mm;
[0147] Fused zirconium mullite ultrafine material: particle size greater than 0.1mm and less than or equal to 0.5mm;
[0148] Fused zirconium mullite powder: D50 is 10~20μm.
[0149] Sintered zirconium mullite was purchased from Guangdong Xinlingnan Technology Co., Ltd.; the following sintered zirconium mullite with different particle sizes was obtained by crushing and screening sintered mullite with the same composition.
[0150] Sintered zirconium mullite coarse material: greater than 3mm and less than or equal to 5mm;
[0151] Sintered zirconium mullite medium material: greater than 1.5mm and less than or equal to 3mm;
[0152] Sintered zirconium mullite fine material: greater than 0.5mm and less than or equal to 1.5mm;
[0153] Sintered zirconium mullite ultrafine material: particle size greater than 0.1mm and less than or equal to 0.5mm.
[0154] The alumina powder includes the following components: the mass fraction of Al2O3 is 99.2%, the mass fraction of SiO2 is 0.24%, the mass fraction of Fe2O3 is 0.05%, and the total mass fraction of Na2O and K2O is 0.21%; the ignition loss of the alumina powder is 0.07%.
[0155] The following alumina powders of different particle sizes are obtained by crushing and screening alumina powders of the same composition.
[0156] Alumina powder A1: D50 = 2 μm.
[0157] Alumina powder A2: D50 = 2.3 μm.
[0158] Alumina powder B: D50 = 5.7 μm.
[0159] The zirconia ball powder includes the following components: the mass fraction of ZrO2 is 99.6%, the mass fraction of SiO2 is 0.12%, the mass fraction of Fe2O3 is 0.03%, and the mass fraction of TiO2 is 0.16%.
[0160] Zirconia powder: D50=8.4μm.
[0161] Dispersion enhancer: Attapulgite, D50 = 10.2 μm, its chemical formula is (Mg, Al) 5 [(OH) 2 (Si, Al) 8 O 20 ]·8H2O, including the following components: The mass fraction of component SiO2 is The mass fraction of magnesium is 56.96% and the mass fraction of MgO is 23.83%.
[0162] Kaolin, D50=5.2μm, product model is Maoming Nanquan brand kaolin N4.
[0163] Example 1
[0164] The refractory material preparation method of this embodiment is as follows:
[0165] 1. Weigh the raw materials of each component according to the raw material composition ratio shown in Table 1.
[0166] 2. Mix the prepared fused zirconium mullite, alumina powder and zirconium oxide powder in a mixer for 5 minutes; then add weighed water, wet mix for 7 minutes and then discharge the material to obtain a mixed mud.
[0167] 3. Put the clay into a vacuum machine, evacuate the vacuum, and pour it into the mold under pressure. Stop pouring after it is full. When there is no obvious lower layer of the clay after about 30 minutes, cut it flat and flatten the pouring mouth, and let it stand in place to dry.
[0168] 4. After drying for 150 hours, transfer to a drying room at 70°C and continue drying for 48 hours.
[0169] 5. Place the dried blank in a shuttle kiln for calcination, control the calcination temperature to 1400°C, and the calcination time to 10 hours.
[0170] Through XRD analysis, it is found that the crystal phase of the lip brick prepared in this embodiment includes 45% to 50% of mullite phase, 17% to 20% of corundum phase, 20% to 23% of baddeleyite phase and 10% to 13% of zircon phase.
[0171] Embodiment 2-4
[0172] Examples 2 to 4 adopt a preparation method that is basically the same as that of Example 1, the only difference being that the formula is different, as specifically shown in Table 1.
[0173] Comparative Example 1
[0174] The preparation method of comparative example 1 is basically the same as that of embodiment 1, except that the raw material component formulas are different. Specifically, the raw material formulas of each embodiment and comparative example are shown in Table 1 below:
[0175] Table 1
[0176]
[0177] Performance Testing
[0178] Test methods and result analysis
[0179] Apparent porosity: The apparent porosity of the refractory materials prepared in each embodiment and comparative example was tested according to the method specified in standard GB / T 2997-2015.
[0180] Bulk density: The bulk density of the refractory materials prepared in each embodiment and comparative example was tested according to the method specified in standard GB / T 2997-2015.
[0181] Compressive strength: The compressive strength of the refractory materials prepared in each embodiment and comparative example was tested according to standard GB / T5072-2023.
[0182] Thermal shock resistance: The thermal shock resistance of the refractory materials prepared in the embodiments and comparative examples was tested according to standard DIN51068:2008-11.
[0183] Anti-glass erosion test: In the anti-glass erosion test experiments of the embodiments and comparative examples of the present invention, the glass is Guangdong pure crystal bottle and jar white glass, the glass flow rate is 45m / h, the test strip size is: 15mm×15mm×108mm, and the experimental temperature and time are 1350℃×144h.
[0184] Foaming index: The foaming index of the embodiments and comparative examples of the present invention is the ratio of the number of bubbles with a diameter of >0.2 mm produced by the sample on the glass under stereomicroscope to the observation area (number / mm 2 ).
[0185] Crystalline phase composition: The crystalline phase composition of the refractory materials prepared in each embodiment and comparative example was obtained by testing using an XRD device.
[0186] The test data of the apparent porosity, bulk density, thermal shock resistance, glass erosion resistance and foaming index of the refractory materials prepared in each embodiment and comparative example are shown in Table 3.
[0187] The crystal phase compositions of the refractory materials prepared in the embodiments and comparative examples are shown in Table 4.
[0188] Table 2
[0189]
[0190] From Table 2, it can be seen that the refractory materials prepared in Examples 1 to 4 have lower apparent porosity, higher bulk density, higher compressive strength and better thermal shock resistance. Figure 1 , Figure 1 This is a surface effect diagram of the refractory material prepared in Example 3 after the foaming experiment. Figure 1 It can be seen that there are basically no bubbles larger than 0.2 mm in the refractory material prepared in Example 3.
[0191] Comparative Example 1 Compared with Example 1, sintered zirconium mullite with different particle sizes is used to replace fused zirconium mullite with different particle sizes; the refractory material prepared in Comparative Example 1 has high apparent porosity, low bulk density, and inferior compressive strength and thermal shock resistance to Example 1. Figure 2 , Figure 2 This is a surface effect diagram of the refractory material prepared in Comparative Example 1 after the foaming experiment. Figure 2 It can be seen that the refractory material prepared in Comparative Example 1 contains more bubbles with a diameter greater than 0.3 mm, and its foaming performance is not as good as that of Example 1. Figure 3 a is the anti-glass erosion graph of the refractory brick prepared in comparative example 1, and b is the anti-glass erosion graph of the refractory brick prepared in example 1. Combined with Table 2, the unidirectional erosion amount at 1 / 2 below the liquid level line of the refractory material prepared in comparative example 1 reaches 0.069 mm / 24h, which is much larger than the unidirectional erosion amount at 1 / 2 below the liquid level line of example 1 (0.041 mm / 24h). It can be seen that the anti-glass corrosion performance of comparative example 1 is also inferior to that of example 1.
[0192] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0193] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A refractory material, characterized in that: The raw materials for its preparation include the following components by weight: 55 to 80 parts of fused zirconium mullite, 10 to 15 parts of zirconium oxide powder and 10 to 30 parts of aluminum oxide powder.
2. The refractory material according to claim 1, characterized in that The refractory material contains a crystal phase, and the crystal phase includes a mullite phase, a corundum phase, a baddeleyite phase and a zircon phase.
3. The refractory material according to claim 2, characterized in that In the refractory material, the crystal phases include, by mass content, 45% to 50% of a mullite phase, 17% to 20% of a corundum phase, 20% to 23% of a baddeleyite phase, and 10% to 13% of a zircon phase.
4. The refractory material according to any one of claims 1 to 3, characterized in that: The refractory material meets at least one of the following conditions: (1) The porosity of the fused zirconium mullite is 16% to 17.5%; (2) The components in the fused zirconium mullite meet the following conditions: the mass fraction of ZrO2 is greater than 32.5%, the mass fraction of Al2O3 is greater than 42%, the mass fraction of SiO2 is ≤18%, the mass fraction of TiO2 is ≤0.2%, the mass fraction of Fe2O3 is ≤0.2%, the total mass fraction of Na2O and K2O is ≤0.35%, and the total mass fraction of CaO and MgO is ≤0.35%; (3) The components in the alumina powder meet the following conditions: the mass fraction of Al2O3>98.5%, the mass fraction of SiO2<0.3%, the mass fraction of Fe2O3≤0.1%, and the total mass fraction of Na2O and K2O≤0.35%; the ignition loss of the alumina powder is less than 0.5%; (4) The components in the zirconium oxide powder meet the following conditions: the mass fraction of ZrO2 is greater than 65.5%, the mass fraction of SiO2 is less than 34%, the mass fraction of Fe2O3 is less than or equal to 0.2%, and the mass fraction of TiO2 is less than or equal to 0.35%.
5. The refractory material according to any one of claims 1 to 3, characterized in that: The refractory material meets at least one of the following conditions: (1) The fused zirconium mullite includes fused zirconium mullite coarse material with a particle size greater than 3 mm and less than or equal to 5 mm, fused zirconium mullite medium material with a particle size greater than 1.5 mm and less than or equal to 3 mm, fused zirconium mullite fine material with a particle size greater than 0.5 mm and less than or equal to 1.5 mm, fused zirconium mullite ultrafine material with a particle size greater than 0.1 mm and less than or equal to 0.5 mm, and fused zirconium mullite powder with a D50 of 10 μm to 20 μm; (2) The D50 of the zirconium oxide powder is 5 μm to 15 μm; (3) The alumina powder includes alumina powder A with a D50 of 1.5 μm to 2.5 μm and alumina powder B with a D50 of 3 μm to 6 μm.
6. The refractory material according to claim 5, characterized in that The preparation materials include the following by weight: 10 to 35 parts of the fused zirconium mullite coarse material, 5 to 25 parts of the fused zirconium mullite medium material, 3 to 15 parts of the fused zirconium mullite fine material, 15 to 25 parts of the fused zirconium mullite ultrafine material, 5 to 10 parts of the fused zirconium mullite powder, 8 to 20 parts of the aluminum oxide powder A, 2 to 10 parts of the aluminum oxide powder B, and The zirconium oxide powder is 10 to 15 parts.
7. The refractory material according to claim 5, characterized in that Calculated by mass percentage, the alumina powder A consists of 40% to 60% of alumina powder A1 and 40% to 60% of alumina powder A2; the D50 of the alumina powder A1 is 2 μm±0.1 μm; and the D50 of the alumina powder A2 is 2.3 μm±0.1 μm.
8. The refractory material according to any one of claims 1 to 3, 6 to 7, characterized in that: The refractory material meets at least one of the following conditions: (1) The raw materials for preparation further include 0.2 to 0.4 parts of a dispersion enhancer; (2) The preparation raw materials also include 5 to 7 parts of water.
9. The refractory material according to claim 8, characterized in that The dispersion enhancer is an inorganic clay; the inorganic clay satisfies at least one of the following conditions: (1) The chemical components in the inorganic clay meet the following conditions: the mass fraction of Al2O3 is less than 15%, the mass fraction of SiO2 is greater than 50%, the mass fraction of CaO is ≤5%, and the mass fraction of MgO is ≤25%; (2) The D50 of the inorganic clay is 3 μm to 15 μm; (3) The inorganic clay includes at least one of attapulgite and kaolin.
10. The method for preparing a refractory material according to any one of claims 1 to 9, characterized in that: The steps include: The raw materials are mixed and then cast to obtain a blank; The blank is calcined to obtain the refractory material.
11. The preparation method according to claim 10, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The casting molding adopts vacuum casting molding; the vacuum degree of vacuum casting molding is -0.08MPa~-0.1MPa; the molding pressure is: 0.2MPa~0.4MPa; (2) Before calcining the blank, the method further comprises drying the blank; The drying step comprises: firstly air-drying the blank for 120 hours to 240 hours, and then drying at 40° C. to 80° C. for 48 hours to 96 hours; (3) The calcination temperature is 1300°C to 1500°C; the calcination time is 8h to 15h.
12. Use of the refractory material according to any one of claims 1 to 8 in the preparation of refractory products.
13. A refractory brick, characterized in that: Contains the refractory material according to any one of claims 1 to 8.
14. A glass melting furnace, characterized in that: Comprising the refractory brick as claimed in claim 13.
Citation Information
Patent Citations
Sintered zircon particle
CN103906723A
Glass melting furnace regenerator top special-use compound spinel zirconium brick and producing method thereof
CN105541351A
Steel ladle carbon-free pouring nozzle and preparation method thereof
CN110642633A
Homogenous body re-sintered fused zirconium mullite brick and preparation method thereof
CN112573932A
Refractory material as well as preparation method and application thereof
CN112759407A